Polyester Film
Patent Information
- Application Number
- JP2021548789
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-24
- Filing Date
- 2020-09-10
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-09-10
AI Technical Summary
【0008】 本発明によれば、高い遮光性を有すると共に、表面平滑性に優れたポリエステルフィルムを提供することができる。例えば、通信機能を搭載した端末機器(スマートフォン、I-Padなど)用部材として好適である。
Smart Images

Figure 0007632292000001 
Figure 0007632292000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester film, for example, a polyester film used in applications requiring light-shielding properties. [Background technology]
[0002] Conventionally, small electronic devices such as smartphones and personal computers have used metal housings, but from the viewpoint of weight reduction and design of electronic devices, attempts have been made to use glass for at least a part of the metal housing. When a part of the housing is made of glass, it has been considered to laminate a resin film having a light-shielding property on the glass in order to prevent the inside from being seen. In addition, a resin film having a light-shielding property may be used around the display in order to prevent the inside of the device from being seen.
[0003] It is known that resin films can be given light-shielding properties by blending pigments in them. For example, Patent Document 1 describes a film containing a black pigment, which is characterized in that the surface roughness (SRa) of at least one side of the film is 100 to 150 nm and the breaking strength in the film width direction is 200 MPa or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-130950 A Summary of the Invention [Problem to be solved by the invention]
[0005] When a black pigment such as carbon black is blended with a resin as in Patent Document 1, sufficient light-blocking properties can be imparted to the film. However, the carbon black aggregates in the resin, increasing the roughness of the film surface and impairing the surface smoothness of the film. In this case, if a metal layer is formed by sputtering or the like in order to impart a metallic luster to the resin film, the unevenness is emphasized, and the design is impaired. In addition, when other pigments are used, the surface smoothness of the film may be impaired in a similar manner. Furthermore, if there is a difference in surface smoothness between the front and back of the polyester film, when a metal layer is provided, distortion of the reflected image occurs, and good visibility may not be obtained.
[0006] The present invention has been made in consideration of the above-mentioned conventional problems, and an object of the present invention is to provide a polyester film which has high light-shielding properties, excellent surface smoothness, and small difference in gloss between the front and back surfaces. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that a polyester film having excellent light-blocking properties and surface smoothness can be obtained by providing a polyester layer (B) having a specific structure on the surface of a polyester layer (A) containing a pigment and by setting the transmission density to a predetermined value or more, and have completed the present invention as described below. That is, the present invention relates to the following [1] to
[16] . [1] A polyester film comprising a polyester layer (A) containing a black pigment and a polyester layer (B) on at least one side of the polyester layer (A), the polyester layer (B) is substantially free of particles or contains particles (X) having an average particle size of 1.0 μm or less; The polyester film has a transmission density (OD value) of 0.4 or more, and a difference in gloss (Gs60°) between the front and back of the film is 3.0 or less. [2] The polyester film according to the above [1], wherein the black pigment is carbon black, and the content of carbon black in the polyester layer (A) is 0.1 to 5.0% by mass. [3] The polyester film according to the above [1] or [2], wherein the content of the particles (X) in the polyester layer (B) is 0.01 to 1.0% by mass. [4] The polyester film according to any one of the above [1] to [3], wherein a ratio of a thickness of the polyester layer (B) to a thickness of the polyester layer (A) [thickness of (B) / thickness of (A)] is from 0.025 to 0.25. [5] The polyester film according to any one of the above [1] to [4], wherein the arithmetic mean height (Sa) of the surface on the polyester layer (B) side of the polyester film is 20.0 nm or less. [6] The polyester film according to any one of the above [1] to [5], wherein the maximum height (Sp) of the surface on the polyester layer (B) side of the polyester film is 1,000 nm or less. [7] The polyester film according to any one of the above [1] to [6], further comprising a polyester layer (B) on both sides of the polyester layer (A). [8] The laminated polyester film according to any one of the above [1] to [7], further comprising a cured resin layer on at least one surface of the polyester layer (B). [9] A polyester film having a metal layer, comprising the polyester film according to [8] above and a metal layer laminated thereon via a cured resin layer.
[10] A polyester film with a metal layer, comprising the polyester film according to any one of the above [1] to [7], and a metal layer directly laminated on at least one surface of the polyester layer (B).
[11] A film laminate comprising an optical member laminated on a surface of the metal layer of the metal-layer-coated polyester film according to [9] or
[10] above, via an adhesive layer.
[12] The film laminate according to the above
[11] , wherein the optical member is a resin film or a glass substrate.
[13] The film laminate according to
[11] or
[12] above, having a total thickness of 150 μm or less.
[14] The polyester film according to any one of the above [1] to [8], which is for a communication terminal.
[15] The polyester film with a metal layer(s) according to the above [9] or
[10] , which is for use in a communication terminal.
[16] The film laminate according to any one of the above
[11] to
[13] , which is for a communication terminal. Effect of the Invention
[0008] According to the present invention, a polyester film having high light-shielding properties and excellent surface smoothness can be provided. For example, the film is suitable as a member for terminal devices (smartphones, I-Pads, etc.) equipped with communication functions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Polyester film] The polyester film of the present invention is a polyester film comprising a polyester layer (A) containing a black pigment and a polyester layer (B) on at least one side of the polyester layer (A). In this polyester film, the polyester layer (B) does not substantially contain particles or contains particles (hereinafter also referred to as particles (X)) having an average particle size of 1.0 μm or less, and the transmission density (OD value) of the polyester film is 0.4 or more. Although the pigment may aggregate in the polyester layer (A) of the polyester film, the polyester layer (B) which is substantially free of particles or has particles with a small average particle size is provided as a surface layer, so that the surface smoothness of the polyester film can be prevented from being impaired by the aggregation of the pigment. Therefore, when a metal is vapor-deposited on the polyester film of the present invention by, for example, sputtering, an excellent metallic luster can be imparted to the film without emphasizing the unevenness of the film surface. Furthermore, the polyester film of the present invention has a high light-blocking property because it contains a large amount of pigment and has a transmission density of 0.4 or more. When used for the housing of an electronic device, the inside of the housing cannot be seen through the film, improving the design. The configuration of the present invention will be described in detail below.
[0010] <Polyester> In the present invention, the polyester used as the raw material for the polyester layer (A) and the polyester layer (B) is not particularly limited, but is preferably a polycondensation polymer of a dicarboxylic acid and a diol, and the dicarboxylic acid is preferably an aromatic dicarboxylic acid, and the diol is preferably an aliphatic diol. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, orthophthalic acid, biphenyldicarboxylic acid, diphenylether-dicarboxylic acid, diphenylsulfone-dicarboxylic acid, diphenylketone-dicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. Among these, terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid are preferred, and terephthalic acid is more preferred.
[0011] Examples of the aliphatic diol include aliphatic diols having a straight or branched structure such as ethylene glycol, 2-butene-1,4-diol, trimethylene glycol, tetramethylene glycol, hexamethylene glycol, neopentyl glycol, methylpentanediol, and diethylene glycol; and alicyclic diols such as cyclohexanedimethanol, isosorbide, spiroglycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, norbornene dimethanol, and tricyclodecane dimethanol. Among these, ethylene glycol, neopentyl glycol, and cyclohexanedimethanol are preferred, and ethylene glycol is more preferred.
[0012] The polyester used in the present invention is preferably a polyester resin in which 50 mol % or more of the dicarboxylic acid units are structural units derived from terephthalic acid and 50 mol % or more of the diol units are structural units derived from ethylene glycol, i.e., polyethylene terephthalate, which makes the polyester resin less likely to become amorphous and has good transparency and light resistance. In polyethylene terephthalate, preferably 70 mol % or more, more preferably 90 mol % or more of the dicarboxylic acid units are structural units derived from terephthalic acid, and preferably 70 mol % or more, more preferably 90 mol % or more of the diol units are structural units derived from ethylene glycol.
[0013] When polyethylene terephthalate is used as the polyester resin, the polyester resin may be composed of polyethylene terephthalate alone, or may contain, in addition to polyethylene terephthalate, a polyester resin other than polyethylene terephthalate. In the present invention, the amount of polyethylene terephthalate in the total amount of polyester resin is preferably from 80 to 100% by mass, and more preferably from 90 to 100% by mass.
[0014] The polyethylene terephthalate used in the present invention is preferably composed only of structural units derived from terephthalic acid and ethylene glycol, but may also contain structural units derived from a bifunctional compound other than terephthalic acid and ethylene glycol. The difunctional compounds include the aromatic dicarboxylic acids and aliphatic diols other than terephthalic acid and ethylene glycol, and difunctional compounds other than aromatic dicarboxylic acids and aliphatic diols.
[0015] Examples of the bifunctional compound other than the aromatic dicarboxylic acid and the aliphatic diol include linear or branched aliphatic bifunctional compounds, and specific examples thereof include aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, azelaic acid, and sebacic acid; and aliphatic hydroxycarboxylic acids such as 10-hydroxyoctadecanoyl acid, lactic acid, hydroxyacrylic acid, 2-hydroxy-2-methylpropionic acid, and hydroxybutyric acid. Also included are alicyclic difunctional compounds such as alicyclic dicarboxylic acids, for example, cyclohexanedicarboxylic acid, norbornenedicarboxylic acid, and tricyclodecanedicarboxylic acid; and alicyclic hydroxycarboxylic acids, for example, hydroxymethylcyclohexanecarboxylic acid, hydroxymethylnorbornenecarboxylic acid, and hydroxymethyltricyclodecanecarboxylic acid. Further examples include aromatic hydroxycarboxylic acids such as hydroxybenzoic acid, hydroxytoluic acid, hydroxynaphthoic acid, 3-(hydroxyphenyl)propionic acid, hydroxyphenylacetic acid, and 3-hydroxy-3-phenylpropionic acid; and aromatic diols such as bisphenol compounds and hydroquinone compounds. The content of the constitutional units derived from the bifunctional compound is preferably 20 mol % or less, and more preferably 10 mol % or less, based on the total moles of all constitutional units constituting the polyester resin.
[0016] When the polyethylene terephthalate used in the present invention contains a constituent unit derived from an aromatic dicarboxylic acid other than terephthalic acid, the aromatic dicarboxylic acid is preferably one or more selected from isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid, which are low in cost and copolymer polyester resins containing one of these are easy to produce. When polyethylene terephthalate contains structural units derived from these aromatic dicarboxylic acids, the proportion of the structural units derived from the aromatic dicarboxylic acids is preferably 1 to 20 mol %, and more preferably 1 to 10 mol %, of the dicarboxylic acid units. When the polyethylene terephthalate used in the present invention contains a constituent unit derived from an aliphatic diol other than ethylene glycol, the aliphatic diol is preferably diethylene glycol. The proportion of the constituent derived from diethylene glycol is preferably 0.1 to 10 mol % and more preferably 0.4 to 5 mol % of the diol unit. The intrinsic viscosity of the polyester resin used in the present invention is not particularly limited, but from the viewpoints of film formability, productivity, etc., it is preferably 0.45 to 1.0 dl / g, more preferably 0.5 to 0.9 dl / g.
[0017] The amount of polyester in each of the polyester layer (A) and the polyester layer (B) is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. When the amount of polyester is equal to or more than the lower limit, the flexibility, strength, etc. of the polyester film can be ensured.
[0018] <Polyester layer (A)> The polyester film of the present invention has a polyester layer (A) containing a black pigment. The polyester film has a light-shielding property due to the polyester layer (A) containing a black pigment.
[0019] [Pigments] The black pigment used in the polyester layer (A) is preferably a black pigment with high hiding power from the viewpoint of the light-shielding property and surface smoothness of the polyester film. By using a black pigment with high hiding power, the light-shielding property of the polyester film, i.e., the transmission density (OD value), can be improved even in a small amount, and the roughness of the polyester film surface can be suppressed if the amount is small. Examples of black pigments include inorganic black pigments such as carbon black (furnace black, channel black, acetylene black, thermal black, lamp black, etc.), carbon nanotubes, graphite, copper oxide, manganese dioxide, titanium black, activated carbon, ferrite, magnetite, chromium oxide, iron oxide, molybdenum disulfide, etc., and organic black pigments such as aniline black, perylene black, cyanine black, chromium complexes, composite oxide-based black pigments, anthraquinone-based organic black pigments, etc., and inorganic black pigments are preferred from the viewpoint of hiding power. These black pigments may be used alone or in combination of two or more.
[0020] Among these black pigments, inorganic black pigments are more preferable from the viewpoint of light-shielding effect, and among these, carbon black is particularly preferable.
[0021] When carbon black is used, its average primary particle size is preferably from 5 to 100 nm, more preferably from 10 to 50 nm, and even more preferably from 15 to 40 nm. When the average primary particle size is equal to or less than the upper limit, the dispersibility in the polyester layer (A) is improved, and the surface smoothness of the polyester film is improved. On the other hand, carbon black may exist as aggregates formed by aggregation of fine primary particles, and when these aggregates are present in a polyester and subjected to biaxial stretching, the stretching stress applied to the film also acts on these aggregates, causing them to disperse. When the average primary particle size is equal to or more than the lower limit, the cohesive force between the primary particles is not too strong, and the aggregates are easily dispersed by the stretching stress when the film is stretched, preventing the carbon black aggregates from becoming large. In the present invention, the average primary particle size is a particle size measured by observing carbon black particles alone or in a polyester with an electron microscope, and when the particles are present as aggregates, it refers to the particle size of the primary particles that constitute the aggregates.
[0022] The content of the black pigment in the polyester layer (A) is preferably 0.1 to 25.0% by mass, more preferably 0.5 to 20.0% by mass, even more preferably 1.0 to 10.0% by mass, and even more preferably 1.5 to 5.0% by mass. When the content of the black pigment is equal to or more than the lower limit, the polyester film can be given sufficient light-shielding properties, and the OD value can be easily increased. On the other hand, when the content of the black pigment is equal to or less than the upper limit, the black pigment is easily dispersed in the polyester layer, and the surface smoothness is improved. Note that, when the content of the black pigment is increased, the black pigment is easily aggregated, but even if the black pigment aggregates, the surface smoothness can be ensured by providing the polyester layer (B).
[0023] In particular, when the black pigment is carbon black, the carbon black content is preferably 0.1 to 5.0 mass%, more preferably 0.5 to 4.0 mass%, and even more preferably 1.2 to 3.0 mass%. If the carbon black content is within the above range, sufficient light blocking properties can be obtained while keeping the amount of pigment used low. In addition, although carbon black may aggregate, if the content is within the above range, the provision of the polyester layer (B) can ensure excellent surface smoothness without impairing surface smoothness due to aggregation.
[0024] In addition to the above-mentioned pigment, the polyester layer (A) may contain conventionally known antioxidants, ultraviolet absorbers, heat stabilizers, lubricants, etc., as required.
[0025] <Polyester layer (B)> The polyester layer (B) is a polyester layer provided on at least one surface of the polyester layer (A) and is a layer that contains substantially no particles or contains particles (X) having an average particle size of 1.0 μm or less. In the present invention, by providing the polyester layer (B) that contains substantially no particles or has particles with a small average particle size on the surface of the polyester layer (A) containing a pigment, excellent surface smoothness can be obtained, and thereby excellent visibility can be obtained.
[0026] In the present invention, it is sufficient that the polyester layer (B) is provided on at least one side of the polyester layer (A), but the polyester layer (B) may be provided on both sides of the polyester layer (A). By providing the polyester layer (B) on both sides of the polyester layer (A), the surface smoothness of both sides can be improved. In addition, by providing the polyester layer (B) on both sides, the gloss difference is easily reduced, and there is no need to check the film side on which the metal layer is to be provided beforehand every time it is processed, which has the advantage of improving work efficiency.
[0027] [Particle (X)] The average particle size of the particles (X) in the polyester layer (B) is 1.0 μm or less as described above. If the average particle size is larger than 1.0 μm, the surface smoothness of the polyester film decreases. The average particle size of the particles (X) in the polyester layer (B) is preferably 0.01 to 0.8 μm, more preferably 0.02 to 0.4 μm, and more preferably 0.02 to 0.15 μm. By setting the average particle size of the particles to the upper limit value or less, the surface smoothness can be improved. On the other hand, by setting the average particle size to the lower limit value or more, slipperiness and the like can be easily imparted to the surface of the polyester film.
[0028] In the present invention, when the particles (X) are in the form of a powder, the average particle size of the particles (X) can be determined by measuring the powder using a centrifugal sedimentation type particle size distribution analyzer (SA-CP3 type) to determine the particle size at an integrated volume fraction of 50% (d50) in the equivalent sphericity distribution. In the present invention, the average particle size of the particles (X) in the polyester film is determined by observing the film using, for example, a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, "S3400N"), measuring the size of one particle from the obtained image data, and averaging the size of 10 points (10 particles) to obtain the average particle size.
[0029] Examples of the particles (X) contained in the polyester layer (B) include inorganic particles such as silica, aluminum oxide, calcium carbonate, and kaolin, and organic polymer particles. From the viewpoint of effectively improving the surface smoothness and from the viewpoint of production costs, inorganic particles are preferred, and aluminum oxide such as spherical alumina, calcium carbonate, and silica are more preferred. Furthermore, from the viewpoint of reducing the average particle size to reduce the surface smoothness and improving the slipperiness, aluminum oxide is even more preferred.
[0030] In the polyester layer (B), the content of the particles (X) is preferably 0.01 to 1.0% by mass. By making the content 0.01% by mass or more, the effect of containing the particles can be exhibited, for example, the slipperiness of the polyester film surface can be improved. In addition, by making the content 1.0% by mass or less, the smoothness of the surface can be improved, for example, when a metal layer is formed on the surface of the polyester film, a film having excellent metallic luster can be obtained. From the above viewpoint, the content of the particles (X) is preferably 0.05 to 0.5% by mass, more preferably 0.1 to 0.4% by mass.
[0031] In addition, an embodiment in which the polyester layer (B) does not substantially contain particles is also preferred. Here, "substantially not containing particles" means that the content of particles in the polyester layer (B) is less than 100 ppm by mass. The polyester layer (B) may contain minute amounts of particles such as polymerization catalysts (e.g., antimony trioxide, etc.) and impurities inevitably mixed in during the manufacturing process, in addition to the above-mentioned particles (X), as described above, but even if a minute amount of particles is contained, the effect on smoothness is minor, and the surface smoothness is well maintained. Note that, in an embodiment in which substantially no particles are contained, the particles contained in a minute amount in the polyester layer (B) preferably have an average particle size of 1 μm or less, but the average particle size may exceed 1 μm. In order to further minimize the effect of the particles on smoothness, the particle content in the polyester layer (B) is preferably 50 ppm by mass or less, more preferably 30 ppm by mass or less, and even more preferably 1 ppm by mass or less. In addition to the above-mentioned particles, the polyester layer (B) may contain conventionally known antioxidants, ultraviolet absorbers, heat stabilizers, lubricants, etc., as required.
[0032] <Transmission density (OD value)> The transmission density (OD value) of the polyester film of the present invention is 0.4 or more. If the transmission density is less than the lower limit, the polyester film does not have sufficient light-shielding properties, and when used in an electronic device, the internal circuits, boards, etc. are visible. From the viewpoint of ensuring sufficient light-shielding properties and preventing the inside of a small electronic device from being visible, the transmission density (OD value) is preferably 1.0 or more, more preferably 3.5 or more, and even more preferably 5.0 or more. In order to make the transmission density (OD value) of the polyester film of the present invention equal to or higher than the above value, a pigment is added to the polyester layer (A) to adjust it. If a pigment with high hiding power is used as the pigment, the transmission density (OD value) can be made equal to or higher than the above value even with a small amount of the pigment added, and the effect on the surface roughness of the polyester film can be reduced because of the small amount of the pigment added.
[0033] <Arithmetic mean height (Sa)> In the present invention, the arithmetic mean height (Sa) on the surface of the polyester layer (B) side of the polyester film is preferably 20.0 nm or less. When the arithmetic mean height (Sa) is the upper limit or less, the smoothness is excellent, and the surface of the polyester film is unlikely to become uneven even after sputtering, for example, so that a polyester film having excellent metallic luster can be obtained. From such a viewpoint, the arithmetic mean height (Sa) is more preferably 15.0 nm or less, and even more preferably 7.0 nm or less. In addition, the arithmetic mean height (Sa) is preferably low from the viewpoint of smoothness, but is, for example, 1.0 nm or more, preferably 2.0 nm or more from the viewpoint of providing a certain degree of slipperiness. In this specification, the arithmetic mean height (Sa) can be measured by the method described in the Examples. In order to set the arithmetic mean height (Sa) on the surface on the polyester layer (B) side of the polyester film of the present invention to the above-mentioned value or less, the type and content of the pigment in the polyester layer (A), the type and content of the particles (X) in the polyester layer (B), the thickness of the polyester layer (B), the thickness ratio of the polyester layer (A) to the polyester layer (B), etc. can be adjusted. The same applies to the maximum height (Sp) described below.
[0034] In this specification, the surface of the polyester layer (B) side of the polyester film means the surface of the polyester layer (B) side when the polyester layer (B) is provided on only one side of the polyester layer (A). When the polyester layer (B) is provided on both sides of the polyester layer (A), it means the surface of either of the polyester layers (B), and the arithmetic average height (Sa) of the surface of either of the polyester layers (B) side may be within the above range, but the arithmetic average height (Sa) of both surfaces of the polyester film may be within the above range. In addition, the surface of the polyester layer (B) side of the polyester film means the surface of the layer (easily adhesive layer, easily lubricating layer, etc.) when a layer such as an easy-adhesion layer or an easy-slip layer is further provided on the surface of the polyester layer (B) of the polyester film as described later, and the arithmetic average height (Sa) of the surface of the layer may be within the above range. The same applies to the maximum height (Sp) described later.
[0035] <Maximum height (Sp)> In the present invention, the maximum height (Sp) on the surface of the polyester layer (B) side of the polyester film is preferably 1,000 nm or less, more preferably 500 nm or less, even more preferably 200 nm or less, and even more preferably 150 nm or less. If the maximum height (Sp) value is large, the film surface is given a grainy feel, but if it is below the upper limit, the grainy feel is reduced and excellent metallic luster can be imparted to the polyester film. In addition, the maximum height (Sp) is preferably low from the viewpoint of reducing the grainy feel, but from the viewpoint of imparting a certain degree of slipperiness, it is, for example, 10.0 nm or more, preferably 20.0 nm or more. In this specification, the maximum height (Sp) can be measured by the method described in the examples.
[0036] <Glossiness (Gs(60°)) Difference> The difference in gloss between the front and back surfaces of the polyester film of the present invention is 3.0 or less, preferably 2.0 or less, and more preferably 1.5 or less. By satisfying the above range, for example, when a metal layer is provided, there is no distortion of reflected image, and good visibility without graininess derived from film can be ensured.Furthermore, if both sides of the film are designed to have the same level of glossiness when providing a metal layer on the film surface, there is no extreme difference in visibility after providing a metal layer regardless of which film surface is used, and work efficiency is improved.If there is a difference in glossiness between the front and back of the film, there is the inconvenience of having to turn the film surface over and process it each time.
[0037] <Thickness> From the viewpoint of sufficiently increasing the light-shielding property of the polyester film of the present invention, the thickness of the polyester layer (A) is preferably from 20 to 70 μm, more preferably from 25 to 60 μm, and further preferably from 30 to 50 μm. The thickness of the polyester layer (B) is preferably 0.5 to 20 μm. By making the thickness 20 μm or less, the thickness of the polyester film can be made thin, and by making the thickness 0.5 μm or more, good surface smoothness can be easily maintained. From these viewpoints, the thickness of the polyester layer (B) is more preferably 1.5 to 15 μm, and even more preferably 4.0 to 10 μm. By making the thickness of the polyester layer (B) 4.0 μm or more, it becomes easier to further reduce unevenness caused by particles (X) having an average particle size of 1 μm or less, and it becomes easier to reduce the above-mentioned Sa and Sp while containing the particles (X).
[0038] In the present invention, the ratio of the thickness of the polyester layer (B) to the thickness of the polyester layer (A) [thickness of (B) / thickness of (A)] is preferably 0.025 to 0.25. When the thickness ratio is within the above range, the light-shielding property and surface smoothness of the polyester film are easily ensured. From this viewpoint, the thickness ratio [(B) / (A)] is more preferably 0.04 to 0.20, and further preferably 0.09 to 0.18. It is generally believed that a highly smooth surface can be obtained if no particles are added to the surface polyester layer, but this is not necessarily the case in many cases when a black pigment is included. For example, in a laminated polyester film, if a large amount of black pigment is added to the polyester layer of the undercoat to obtain a deep black color, the surface of the undercoat layer is likely to form unevenness. Furthermore, the unevenness also affects the polyester layer in contact with the undercoat layer, and the polyester layer in the surface portion is also likely to form unevenness. This problem is not apparent in a colorless and transparent polyester film because it is difficult to see from the outside, and it can be said to be a problem specific to black polyester films. Therefore, from the viewpoint of a countermeasure against this problem, it is effective to adjust the thickness ratio of each polyester layer in the laminated film as described above.
[0039] <Cured resin layer> The polyester film of the present invention may have a cured resin layer on the outermost surface. By providing a cured resin layer, it is possible to reduce heat damage to the base film during the process of forming a metal layer or the like formed by sputtering or to easily improve adhesion to the metal layer. For example, when the cured resin layer is an easy-adhesion layer, it is preferable that it is provided on the surface of the polyester layer (B). When the polyester layer (B) is provided on both sides of the polyester layer (A), the easy-adhesion layer may be provided on the surfaces of both polyester layers (B), but it is sufficient that it is provided on the surface of one of the polyester layers (B).
[0040] The easy-adhesion layer is formed, for example, from an easy-adhesion layer composition containing a binder resin and a crosslinking agent. Examples of the binder resin include polyester resin, acrylic resin, urethane resin, polyvinyl resin such as polyvinyl alcohol, polyalkylene glycol, polyalkyleneimine, methyl cellulose, hydroxycellulose, starch, and the like. Among these, from the viewpoint of improving adhesion to a metal layer, etc., it is preferable to use polyester resin, acrylic resin, and urethane resin. In the easy-adhesion layer composition, the content of the binder resin is, for example, 20 to 90 mass%, preferably 30 to 80 mass%, based on the solid content. As the crosslinking agent, various known crosslinking agents can be used, such as oxazoline compounds, melamine compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, and silane coupling compounds. Among these, oxazoline compounds are preferably used from the viewpoint of improving the durability and adhesion. Furthermore, melamine compounds are preferably used from the viewpoint of improving the durability and coatability of the easy-adhesion layer. The content of the crosslinking agent in the easy-adhesion layer composition is, for example, 5 to 50 mass%, preferably 10 to 40 mass%, based on the solid content. The adhesive layer composition may contain particles within a range that does not impair the adhesiveness of the adhesive layer and the smoothness of the surface of the polyester film. As the particles, those shown in the easy-slip layer described later can be appropriately used. The content of the particles in the adhesive layer composition is, for example, 1 to 20 mass%, preferably 3 to 15 mass%, based on the solid content. The adhesive layer composition may also contain a component for promoting crosslinking, such as a crosslinking catalyst, etc. Furthermore, it is also possible to use a defoamer, a coatability improver, a thickener, an organic lubricant, an antistatic agent, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc. in combination.
[0041] The adhesive layer composition is preferably diluted with water, an organic solvent, or a mixture thereof, and the adhesive layer is preferably formed by coating the outermost surface of the polyester film with a diluted adhesive layer composition as a coating liquid and drying the coating. The coating may be performed by a conventional method. The thickness of the easy-adhesion layer is usually in the range of 0.003 to 1 μm, preferably 0.005 to 0.6 μm, and more preferably 0.01 to 0.4 μm. By making the thickness 0.003 μm or more, sufficient adhesion can be ensured. Also, by making the thickness 1 μm or less, deterioration of appearance and blocking are less likely to occur.
[0042] <Easy layer> The polyester film of the present invention may have a lubrication layer on the outermost surface. By providing the lubrication layer, the slipperiness is improved, and the roll winding property and handling property of the polyester film are improved. The lubrication layer is preferably provided on the surface of the polyester layer (B). When the polyester layer (B) is provided on both sides of the polyester layer (A), the lubrication layer may be provided on the surfaces of both polyester layers (B), but it is sufficient to provide the lubrication layer on the surface of one of the polyester layers (B). In addition, the polyester film of the present invention is preferably provided with the above-mentioned easy-adhesion layer on one surface and the above-mentioned easy-slip layer on the other surface. Therefore, when the polyester layer (B) is provided on both sides of the polyester layer (A), it is preferable that the easy-adhesion layer is provided on the surface of one polyester layer (B) and the easy-slip layer is provided on the surface of the other polyester layer (B). In this way, when the easy-adhesion layer and the easy-slip layer are provided on each surface, the easy-adhesion layer improves the transport between rolls and improves workability, and it is easy to laminate other layers such as a metal layer on the surface of the easy-adhesion layer.
[0043] The easy-slip layer is formed from an easy-slip layer composition containing, for example, a binder resin, a crosslinking agent, and particles. The compounds that can be used for the binder resin and the crosslinking agent are as described above for the binder resin and the crosslinking agent used in the easy-adhesion layer. The content of the binder resin in the lubrication layer composition is, for example, 20 to 90 mass %, preferably 30 to 80 mass %, based on the solid content. The content of the crosslinking agent in the lubrication layer composition is, for example, 5 to 50 mass %, preferably 10 to 40 mass %, based on the solid content.
[0044] Specific examples of particles used in the easy-slip layer include silica, alumina, kaolin, calcium carbonate, organic polymer particles, etc. Among them, silica is preferred from the viewpoint of transparency. The average particle size of the particles is preferably within the range of 0.005 to 1.0 μm, more preferably 0.01 to 0.8 μm, and even more preferably 0.01 to 0.6 μm, from the viewpoint of improving the slipperiness without impairing the surface smoothness of the polyester film. The average particle size can be measured by the same method as that for the above-mentioned particles (X). The content of the particles in the easy-slip layer composition is, for example, 1 to 20 mass %, preferably 3 to 15 mass %, based on the solid content. The particles used in the lubrication layer may be of one type, but it is also preferable to use two types of particles having different average particle sizes in combination.
[0045] The lubrication layer composition is preferably diluted with water, an organic solvent, or a mixture thereof, and the lubrication layer is preferably formed by coating the outermost surface of the polyester film with a diluted solution of the adhesion layer composition as a coating solution and drying the coating. The coating may be performed by a conventionally known method. The thickness of the slippery layer is usually in the range of 0.003 to 1 μm, preferably 0.005 to 0.6 μm, and more preferably 0.01 to 0.4 μm. By making the thickness 0.003 μm or more, the particles contained in the slippery layer can be sufficiently held and slipping properties can be imparted. Also, by making the thickness 1 μm or less, deterioration of appearance and blocking are less likely to occur.
[0046] The polyester film of the present invention is preferably used in applications requiring light-shielding properties and surface smoothness, for example, in electronic equipment applications, particularly in communication terminals. In electronic equipment applications, when the film is used around a housing or a display, it can prevent the electronic board or the like inside the housing from being seen through. In addition, by having surface smoothness, for example, even if a metal layer described later is laminated, the smoothness of the metal layer can be ensured, and the design can be improved.
[0047] <Polyester film with metal layer> The polyester film of the present invention is preferably used as a polyester film with a metal layer by laminating a metal layer on its surface. The metal layer is preferably laminated on the surface of the polyester film on the polyester layer (B) side. By having the metal layer, the polyester film with a metal layer has a metallic luster and can improve the design. Since the surface on the polyester layer (B) side is smooth as described above, the metal layer provided on that surface is also smooth and graininess is less noticeable. When the polyester layer (B) is provided on both sides of the polyester layer (A), the metal layer may be provided on the surfaces of both polyester layers (B), but it is sufficient that the metal layer is provided on the surface of one of the polyester layers (B). In addition, when an easy-adhesion layer is provided on the surface of the polyester layer (B) as described above, it is preferable to laminate a metal layer on the easy-adhesion layer. However, the metal layer may be laminated directly on the surface of the polyester layer (B) without the easy-adhesion layer.
[0048] The thickness of the metal layer is not particularly limited, but is preferably 5 to 900 nm, and more preferably 10 to 300 nm. When the thickness of the metal layer is equal to or greater than the lower limit, the metal layer is less likely to crack, and is strong. On the other hand, when the thickness of the metal layer is equal to or less than the upper limit, the metal layer can be formed in a short time. In addition, by keeping the thickness within the above range, sufficient metallic gloss can be imparted.
[0049] The metal layer can be formed by a conventional method, specifically, by one or more methods selected from the group consisting of vapor deposition, sputtering, and ion plating, and is preferably formed by sputtering from the viewpoint of ease of production. In the sputtering method, a polyester film is preferably placed in a vacuum chamber, an inert gas such as argon is introduced, a direct current voltage is applied, the ionized inert gas is caused to collide with a target metal, and the metal that is knocked out forms a metal layer on the surface of the polyester film.
[0050] In the polyester film with a metal layer of the present invention, since the base film is black, the metal layer can be inspected during the process of forming the metal layer by sputtering until the film is wound up. Usually, when a colorless and transparent base film is used, light is reflected from the back side of the film where no metal layer is provided, so-called backside reflection occurs, and excess light returns, which tends to interfere with inspection. Therefore, in the past, the process of forming the metal layer by sputtering and the inspection process were often separated, and the work efficiency decreased as the number of processes increased. In the polyester film with a metal layer using a black substrate film as in the present invention, the above-mentioned back surface reflection from the substrate film does not occur, and the metal layer can be inspected with high accuracy. Furthermore, by making the surface of the substrate film on the side where the metal layer is provided highly smooth, the light irradiated onto the surface of the metal layer during inspection faces the same direction and is reflected back to the detector, which is advantageous in that the inspection accuracy is further improved.
[0051] <Film laminate> The polyester film with a metal layer of the present invention is preferably used as a film laminate in which an optical member is laminated on the surface of the metal layer via an adhesive layer. Examples of the optical member include resin films such as a polarizer film, a protective film, a retardation film, and a protective film, and also preferably includes a glass substrate of a liquid crystal cell. In addition, assuming the replacement of glass substrates with resin films, when a resin film such as a polyimide film, polyester film, or cyclic polyolefin is laminated to a polyester film with a metal layer via an adhesive layer, it is expected that the thickness will be further reduced in the future from a technical standpoint. Therefore, the total thickness of the film laminate is preferably 150 μm or less, more preferably 130 μm or less, and particularly preferably 100 μm or less. Furthermore, in the film laminate, it is possible to impart folding properties by appropriately selecting the resin films to be combined. This makes it possible to accommodate various display applications such as foldable, bendable, and rollable, and is expected to further expand the range of applications of the film laminate.
[0052] <Production method of polyester film> Next, a method for producing the polyester film of the present invention will be specifically described, but the method is not limited to the following method. First, additives such as the pigment or particles are added to the polyester to produce a raw material for the polyester layer (A) or the polyester layer (B). In producing the raw material, it is particularly preferable to use a twin-screw extruder in order to knead the raw material into the polyester in a well-dispersed manner.
[0053] Next, the raw materials for the polyester layer (A) and the polyester layer (B) are fed into multiple extruders, and the respective polyesters are laminated using a multiple-layer multi-manifold die or feed block, and a molten sheet of multiple layers is extruded from a die, and the sheet is cooled and solidified with a cooling roll to obtain an unstretched sheet. In this case, in order to improve the flatness of the sheet, it is preferable to increase the adhesion between the sheet and the rotating cooling drum, and it is preferable to adopt an electrostatic application adhesion method and / or a liquid application adhesion method.
[0054] The unstretched film is then stretched in biaxial directions to be biaxially oriented. That is, the unstretched sheet is stretched in the machine direction by a roll stretching machine. The stretching temperature is usually 70 to 120°C, preferably 75 to 110°C, and the stretching ratio is usually 2.5 to 7.0 times, preferably 3.0 to 6.0 times. The film is then stretched in the transverse direction at a temperature of usually 70 to 125° C., preferably 80 to 120° C., and a stretch ratio of usually 3.0 to 7.0, preferably 3.5 to 6.0. The film is then heat-treated at a temperature of 170 to 250° C. under tension or relaxation of 30% or less to obtain a biaxially stretched film.
[0055] In the above stretching, a method of stretching in one direction in two or more stages can be used. In that case, it is preferable to perform the stretching so that the final stretching ratios in two directions are each within the above range. It is also possible to perform simultaneous biaxial stretching of the unstretched sheet so that the area stretching ratio is 10 to 40 times. Furthermore, if necessary, the sheet may be stretched again in the longitudinal and / or transverse directions before or after heat treatment.
[0056] The surface of the polyester film obtained by the above-mentioned method can be coated as necessary, and the above-mentioned easy-adhesion layer and easy-slip layer can be formed by coating. The coating can be performed in-line, off-line, or a combination of both, but it is preferable to perform it in-line. In-line coating can use a series of processes in which a coating solution diluted mainly with water is applied at the stage where longitudinal stretching is completed, and then drying, preheating, transverse stretching, and further heat fixing are performed in a tenter.
[0057] Furthermore, the polyester film of the present invention can be continuously produced and wound into a roll to obtain a rolled body of the polyester film.
[0058] <Explanation of terms, etc.> Generally, a "sheet" is defined in JIS as a thin, flat product whose thickness is small relative to its length and width, and generally, a "film" is a thin, flat product whose thickness is extremely small relative to its length and width, and whose maximum thickness is arbitrarily limited, and which is usually supplied in the form of a roll (Japanese Industrial Standards; JIS K6900). However, the boundary between a sheet and a film is unclear, and since there is no need to distinguish between the two in the present invention, in the context of the present invention, the term "film" includes the term "sheet," and the term "sheet" includes the term "film."
[0059] In addition, in this specification, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0060] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0061] [Evaluation method] In the present examples and comparative examples, the following evaluations were carried out. (1) Method for measuring the intrinsic viscosity of polyester 1 g of polyester from which other polymer components incompatible with polyester and pigments had been removed was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.
[0062] (2) Average particle size The equivalent sphericity distribution of the powder particles was measured using a centrifugal sedimentation type particle size distribution analyzer (SA-CP3 type) manufactured by Shimadzu Corporation, and the cumulative volume fraction of each particle size range was calculated. The particle size at a cumulative volume fraction of 50% in the equivalent sphericity distribution in which the particles were measured was taken as the average particle size.
[0063] (3) Film thickness and thickness of each layer A small piece of film was embedded in epoxy resin, and a section was cut out with a microtome so that the cross section in the thickness direction could be observed, and this was observed by a transmission electron microscope photograph. In the cross section, the lamination interface was observed by light and dark almost parallel to the film surface. The distance from the interface to the film surface was averaged for each transmission electron microscope photograph, and the thickness was calculated.
[0064] (4) Average primary particle size of pigment A small piece of polyester film was fixed and molded with epoxy resin, then cut with a microtome, and the cross section of the polyester film was observed with a transmission electron microscope. The maximum diameter (a) of the pigment observed in the cross section of the polyester film and the diameter (b) perpendicular to it were measured, and the primary particle size was calculated using the following formula. The same measurement was performed on 500 randomly selected pigment particles, and the arithmetic mean was taken as the average primary particle size of the pigment. Average primary particle size=(a+b) / 2
[0065] (5) Transmission density (OD value) The transmission density was measured using a portable black-and-white transmission densitometer (Ihara Electronics Co., Ltd., "Ihac-T5"). Measurements were performed at five points, and the average value was taken as the OD value. The higher this value, the lower the light transmittance.
[0066] (6) Arithmetic mean height (Sa) and maximum height (Sp) The surface of the polyester layer (B) side of the polyester film was measured using a non-contact surface / layer cross-sectional shape measurement system VertScan (registered trademark) R550GML manufactured by Ryoka Systems Co., Ltd., with a CCD camera: SONY HR-50 1 / 3', objective lens: 20x, lens barrel: 1X Body, zoom lens: No Relay, wavelength filter: 530 white, measurement mode: Wave, in an area of 640 μm × 480 μm, and the arithmetic mean height (Sa) and maximum height (Sp) were calculated using the output from fourth-order polynomial correction. Ten points were measured, and the average values were taken as the arithmetic mean height (Sa) and maximum height (Sp) of the film surface.
[0067] (7) Evaluation of gloss difference (60°) The gloss of the surface of the polyester layer (B) side (front and back) of the polyester film was measured at an angle of 60° to the measurement sample surface using a gloss meter (VG-2000, manufactured by Nippon Denshoku Industries Co., Ltd.).
[0068] (8) Surface smoothness evaluation (1) An aluminum layer of about 100 nm was deposited on the surface of the polyester layer (B) of the polyester film using a vacuum deposition device so that the entire surface of the polyester film was covered. The film with the aluminum layer formed was turned upside down, and a brown bottle was placed directly opposite the aluminum surface. The reflected image of the brown bottle on the film surface was visually observed, and the smoothness was evaluated according to the following criteria. [Evaluation Criteria] A: The reflected image is clearly visible, and the film surface has excellent smoothness. B: The reflected image is slightly cloudy, but the smoothness of the film surface does not affect its practical application. C: The reflected image is whitish and cloudy, and the film surface is poor in smoothness.
[0069] (9) Surface smoothness evaluation (2) An aluminum layer of about 100 nm was deposited on the surface of the polyester layer (B) side of the polyester film using a vacuum deposition device so that the entire surface of the polyester film was covered. The film was placed on a table with the aluminum layer facing up, and a fluorescent lamp was placed directly above it. The reflected light of the fluorescent lamp on the film surface was visually observed, and the smoothness was evaluated according to the following criteria. [Evaluation Criteria] A: No granular irregularities are visible, and the film surface has excellent smoothness. B: Although slight granular irregularities are visible, the smoothness of the film surface does not pose a problem for practical use. C: Granular irregularities are clearly visible, and the film surface is poor in smoothness.
[0070] [material] The materials used in the examples and comparative examples are shown below. <Polyester A> Polyethylene terephthalate homopolymer with an intrinsic viscosity of 0.65 dl / g. <Polyester B> 80 parts by mass of Polyester A and 20 parts by mass of carbon black particles having an average primary particle size of 20 nm were dry blended and extruded using a twin-screw kneading extruder to obtain Polyester B. The intrinsic viscosity of the obtained Polyester B was 0.58 dl / g. <Polyester C> 99.8 parts by mass of Polyester A and 0.2 parts by mass of silica particles having an average particle size of 3.2 μm were dry blended and extruded using a twin-screw kneading extruder to obtain Polyester C. The intrinsic viscosity of the obtained Polyester C was 0.64 dl / g. <Polyester D> Polyester A is pre-crystallized at 160°C and then solid-phase polymerized in a nitrogen atmosphere at 220°C to produce polyethylene terephthalate having an intrinsic viscosity of 0.78 dL / g, 99% by mass of the ester units being ethylene terephthalate, and the remaining ester units being polymerized diethylene glycol and terephthalic acid. <Polyester E> Polyester A is pre-crystallized at 160°C and then solid-phase polymerized in a nitrogen atmosphere at 220°C to produce polyethylene terephthalate having an intrinsic viscosity of 0.70 dL / g, 99% by mass of the ester units being ethylene terephthalate, and the remaining ester units being polymerized from diethylene glycol and terephthalic acid. <Polyester F> Polyethylene terephthalate containing 330 ppm by mass of antimony atom and 2% by mass of calcium carbonate particles having an average particle size of 0.7 μm, using antimony trioxide as a polymerization catalyst. The intrinsic viscosity was 0.61 dl / g. <Polyester G> Polyethylene terephthalate containing 330 ppm by mass of antimony atoms and 20% by mass of spherical alumina particles having an average particle size of 0.05 μm, using antimony trioxide as a polymerization catalyst. The intrinsic viscosity was 0.61 dl / g.
[0071] [Examples and Comparative Examples] <Example 1> The polyesters A and B were mixed at 90% by mass and 10% by mass, respectively, to form the raw material for the polyester layer (A). The polyesters D and F were mixed at 92.5% by mass and 7.5% by mass, respectively, to form the raw material for the polyester layer (B), which is the surface layer. The laminated polyester resins of two kinds and three layers, each consisting of a B layer / A layer / B layer, were co-extruded into a film shape by a melt extruder, and the sheet was co-extruded onto a casting drum cooled to 20°C, cooled and solidified to obtain a non-oriented sheet. Next, the film was stretched 3.3 times in the machine direction (longitudinal direction) at 80° C., and then the film ends were held with clips and introduced into a tenter, where it was preheated and stretched 4.3 times in the direction perpendicular to the machine direction (transverse direction) at 115° C. After biaxial stretching, it was heat-treated at 234° C. for 3 seconds to obtain a polyester film with a thickness of 50 μm (B layer / A layer / B layer=4.0 μm / 42.0 μm / 4.0 μm).
[0072] <Example 2> A polyester film having a thickness of 50 μm was obtained in the same manner as in Example 1, except that the layer structure and thickness were changed as shown in Table 1.
[0073] <Example 3> The polyesters E and G were mixed in ratios of 98.5% by mass and 1.5% by mass, respectively, to form the raw material for the polyester layer (B). A polyester film having a thickness of 50 μm was obtained in the same manner as in Example 1, except that the layer structure and thickness were changed as shown in Table 1.
[0074] <Example 4> The polyesters A and B were mixed in ratios of 89% by mass and 11% by mass, respectively, to form the raw material for the polyester layer (A). Except for changing the layer structure and thickness as shown in Table 1, a polyester film having a thickness of 50.2 μm was obtained in the same manner as in Example 3.
[0075] <Example 5> A polyester film having a thickness of 50 μm was obtained in the same manner as in Example 1, except that the polyester E was used as the raw material for the polyester layer (B) and the layer configuration and thickness were changed as shown in Table 1. The polyester layer (B) contained less than 100 ppm by mass of particles and was substantially free of particles.
[0076] <Example 6> A polyester film having a thickness of 50 μm was obtained in the same manner as in Example 5, except that the layer structure and thickness were changed as shown in Table 1. The polyester layer (B) contained less than 100 ppm by mass of particles and was substantially free of particles.
[0077] <Comparative Example 1> The polyesters A and B were mixed in ratios of 95% by mass and 5% by mass, respectively, and melt-extruded using a melt extruder. A sheet was co-extruded onto a casting drum cooled to 20°C, and cooled and solidified to obtain a single-layer unoriented sheet. Next, the film was stretched 3.2 times in the machine direction (longitudinal direction) at 80° C., and then the film end was held with clips and introduced into a tenter, where it was preheated and stretched 4.0 times in the direction perpendicular to the machine direction (transverse direction) at 115° C. After biaxial stretching, it was heat-treated at 234° C. for 3 seconds to obtain a polyester film with a thickness of 50 μm.
[0078] <Comparative Example 2> A polyester film having a thickness of 50 μm was obtained in the same manner as in Comparative Example 1, except that the polyesters A and B were mixed in proportions of 90% by mass and 10% by mass, respectively.
[0079] <Comparative Example 3> The polyesters B, C, and D were mixed in proportions of 2 mass%, 3 mass%, and 95 mass%, respectively, and melt-extruded using a melt extruder. A sheet was co-extruded onto a casting drum cooled to 20°C, and cooled and solidified to obtain a single-layer unoriented sheet. Next, the film was stretched 2.8 times in the machine direction (longitudinal direction) at 87°C, and then the film end was held with clips and introduced into a tenter, where it was preheated and stretched 3.4 times in the direction perpendicular to the machine direction (transverse direction) at 115°C. After biaxial stretching, it was heat-treated at 228°C for 3 seconds to obtain a polyester film with a thickness of 188 μm. [Table 1]
[0080] [Table 2]
[0081] As is clear from the above examples, by providing a polyester layer (B) that does not substantially contain particles or that contains particles (X) with an average particle size of 1.0 μm or less on the surface of a polyester layer (A) containing a black pigment, both the light blocking property and the surface smoothness are improved. Furthermore, the gloss difference is also reduced, so that visibility is improved even if a metal layer is provided on either side. As is clear from the results in Table 1, Examples 3 and 4, in which the polyester layer (B) is relatively thick and uses alumina with a small particle size, and Examples 5 and 6, in which the polyester layer (B) does not contain particles, are particularly excellent in light blocking properties and surface smoothness. Among these, Examples 3, 4, and 6, in which the polyester layer (B) is thick, are preferred from the viewpoint of surface smoothness, and Examples 3 and 4, in which the slipperiness is improved by using alumina particles, are preferred from the viewpoint of workability. In Comparative Example 3, the glossiness of the front and back is different, so the reflected image is distorted, and the film has a hazy texture due to the graininess of the film, and the visibility of the rough side is reduced. Therefore, it is not suitable for a surface on which a metal layer is to be provided, so there is the inconvenience of having to turn the film side over when using the film.
Claims
1. A film laminate comprising a polyester film having a polyester layer (A) containing a black pigment and polyester layers (B) on both sides of the polyester layer (A), a cured resin layer on at least one side of the polyester layer (B), a metal layer laminated on the cured resin layer, and an optical member laminated on the surface of the metal layer via an adhesive layer, the polyester layer (B) of the polyester film is substantially free of particles or contains particles (X) having an average particle size of 1.0 μm or less; The polyester film has a transmission density (OD value) of 0.4 or more, and a difference in gloss (Gs60°) between the front and back of the film is 3.0 or less.
2. A film laminate comprising a polyester film having a polyester layer (A) containing a black pigment and polyester layers (B) on both sides of the polyester layer (A), a metal layer directly laminated on at least one side of the polyester layer (B), and an optical member laminated on the surface of the metal layer via an adhesive layer, the polyester layer (B) of the polyester film is substantially free of particles or contains particles (X) having an average particle size of 1.0 μm or less; The polyester film has a transmission density (OD value) of 0.4 or more, and a difference in gloss (Gs60°) between the front and back of the film is 3.0 or less.
3. 3. The film laminate according to claim 1, wherein the black pigment is carbon black, and the content of carbon black in the polyester layer (A) is 0.1 to 5.0 mass %.
4. The film laminate according to any one of claims 1 to 3, wherein the content of the particles (X) in the polyester layer (B) is 0.01 to 1.0 mass %.
5. The film laminate according to any one of claims 1 to 4, wherein the ratio of the thickness of the polyester layer (B) to the thickness of the polyester layer (A) [thickness of (B) / thickness of (A)] is 0.025 to 0.
25.
6. The film laminate according to any one of claims 1 to 5, wherein the arithmetic mean height (Sa) of the surface of the polyester layer (B) of the polyester film is 20.0 nm or less.
7. The film laminate according to any one of claims 1 to 6, wherein the maximum height (Sp) of the polyester layer (B) on the surface of the polyester film is 1,000 nm or less.
8. The film laminate according to any one of claims 1 to 7, wherein the optical member is a resin film or a glass substrate.
9. The film laminate according to any one of claims 1 to 8, having a total thickness of 150 µm or less.
10. The film laminate according to any one of claims 1 to 9, which is for a communication terminal.
11. A polyester film having a black pigment-containing polyester layer (A) and polyester layers (B) on both sides of the polyester layer (A), a cured resin layer is provided on at least one side of the polyester layer (B), and a metal layer is laminated on the cured resin layer, the polyester layer (B) is substantially free of particles or contains particles (X) having an average particle size of 1.0 μm or less; The polyester film with a metal layer has a transmission density (OD value) of 0.4 or more and a difference in gloss (Gs60°) between the front and back of the film of 3.0 or less, and is used for a communication terminal.
12. A polyester film having a polyester layer (A) containing a black pigment and polyester layers (B) on both sides of the polyester layer (A), and a metal layer is directly laminated on at least one side of the polyester layer (B), the polyester layer (B) is substantially free of particles or contains particles (X) having an average particle size of 1.0 μm or less; The polyester film with a metal layer has a transmission density (OD value) of 0.4 or more and a difference in gloss (Gs60°) between the front and back of the film of 3.0 or less, and is used for a communication terminal.
13. 13. The polyester film with a metal layer(s) according to claim 11 or 12, wherein the black pigment is carbon black, and the content of carbon black in the polyester layer (A) is 0.1 to 5.0 mass %.
14. The polyester film with a metal layer(s) according to any one of claims 11 to 13, wherein the content of the particles (X) in the polyester layer (B) is 0.01 to 1.0 mass%.
15. The polyester film with a metal layer(s) according to any one of claims 11 to 14, wherein a ratio of a thickness of the polyester layer (B) to a thickness of the polyester layer (A) [thickness of (B) / thickness of (A)] is 0.025 to 0.
25.
16. The polyester film with a metal layer(s) according to any one of claims 11 to 15, wherein the arithmetic mean height (Sa) of the surface of the polyester layer (B) of the polyester film is 20.0 nm or less.
17. The polyester film with a metal layer(s) according to any one of claims 11 to 16, wherein the maximum height (Sp) of the polyester layer (B) on the surface of the polyester film is 1,000 nm or less.
Citation Information
Patent Citations
Biaxial oriented laminated polyester film
JP1988042862A
Colored polyester film
JP2007045895A
Lightproof polyester film
JP2008056871A
Biaxially oriented polyester film for vapor deposition
JP2011131391A
Laminated film for molding and molded article using the same
JP2016168833A